Utilization of AI in Credit Risk Analysis - Wahlberg, Olivia (My University, 2024)
This research investigates how artificial intelligence could be utilized in credit risk analysis. Credit risk analysis is an essential part of credit ratings. This research concludes how to use artificial intelligence to minimize limitations of credit ratings and to facilitate and enhance the analyst’s work when analysing credit risks. These themes will be considered with a literature review and credit risk manager’s interview. This research introduces one kind of credit rating process as a whole. The probability of default and expected loss are essential metrics when assessing credit rating. In addition to the probability of default and expected loss, credit risk analysis can comprise six segments: ownership and corporate structure, governance and management, business and competitiveness, industry and markets, financial structure and debt servicing capacity and sustainability risks. Relevant sub-divisions of artificial intelligence are introduced to give an adequate overview of the capabilities of artificial intelligence. When introducing the limitations and deficiencies of credit ratings, this research analyses how to utilize artificial intelligence to enhance the credit rating process and eliminate the limitations of credit ratings. This research concludes that the limitations of credit ratings could be eliminated with credit rating artificial intelligence models introduced in the academic field. This research introduces two artificial neural network models to facilitate the analyst’s work and enhance the analysis. The first model helps analysts filter and adjust financial information to comparable. The second model helps analysts before the analysis when filtering if the target of the analysis can even get credit. This reduces the amount of analysis, and analysts can focus more on the rest of the analysis. The utilization of artificial intelligence in credit risk assessment has multiple limitations, such as information leak risks, ethical points of view, and the efficiency of cooperation between artificial intelligence and humans. The significance of the limitations explains the minimal use of artificial intelligence in credit risk assessments.

Tutkielma selvittää miten tekoälyä voitaisiin hyödyntää luottoriskianalyysissä laajemmin. Luottoriskianalyysi on tärkeä osa luottoluokitusten tekoa. Tutkielma analysoi, kuinka hyödyntää tekoälyä luottoluokitusten rajoitteiden minimoimiseksi ja analyytikon työn tehostamiseksi arvioitaessa luottoriskejä. Tutkielma on tehty kirjallisuuskatsauksen ja luottoriskipäällikön haastattelun pohjalta. Tutkielma esittelee erään mahdollisen luottoluokitusprosessin kokonaisuudessaan. Maksukyvyttömyyden todennäköisyys ja odotettu tappio ovat tärkeitä mittareita luottoluokituksen arvioinnissa. Näiden mittareiden lisäksi luottoriskien arviointi voi koostua esimerkiksi kuudesta osasta: omistus ja yhtiörakenne, hallinto ja johtaminen, liiketoimintamalli ja kilpailukyky, toimiala ja markkinat, rahoitusrakenne ja velanhoitokyky ja kestävyysriskit. Tekoälyn oleellisimmat osa-alueet on esitelty antamaan riittävä kokonaiskuva tekoälyn kyvyistä. Tutkielman esiteltyä luottoluokitusten rajoitteet ja puutteet, analysoidaan kuinka tehostaa luottoluokitusprosessia ja eliminoida luottoluokitusten rajoitteita tekoälyn avulla. Tutkielma päätyy lopputulokseen, että luottoluokitusten rajoitteita voitaisiin eliminoida akateemisella alalla esitettyjen luottoluokituksen tekevien tekoäly mallien avulla. Tutkielmassa esitellään kaksi neuroverkkomallia edistämään ja tehostamaan analyytikon työtä ja analyysiä. Ensimmäinen malli auttaa analyytikkoa haravoimaan ja muuntamaan taloudellisia raportteja vertailukelpoisiksi. Toinen malli olisi analyytikon avuksi ennen analyysiä, kun arvioidaan, mitkä analyysit kannattaa edes tehdä ja kenellä ei ole mitään mahdollisuutta saada esimerkiksi lainaa. Tällöin analyysien määrä vähenee, ja analyytikko pystyy tekemään muut analyysit huolellisemmin. Tekoälyn hyödyntäminen luottoriskianalyysissä sisältää paljon rajoitteita, kuten tietovuotoriskin, eettiset näkökulmat ja tekoälyn ja ihmisen välisen yhteistyön tehokkuuden. Rajoitteiden merkittävyys selittää tekoälyn vähäisen hyödyntämisen luottoriskianalyyseissä tähän mennessä.
Keywords: credit rating, credit risk assessment, artificial intelligence, artificial neural networks